2021
DOI: 10.1515/nanoph-2020-0576
|View full text |Cite
|
Sign up to set email alerts
|

Towards lab-on-chip ultrasensitive ethanol detection using photonic crystal waveguide operating in the mid-infrared

Abstract: Thanks to the unique molecular fingerprints in the mid-infrared spectral region, absorption spectroscopy in this regime has attracted widespread attention in recent years. Contrary to commercially available infrared spectrometers, which are limited by being bulky and cost-intensive, laboratory-on-chip infrared spectrometers can offer sensor advancements including raw sensing performance in addition to use such as enhanced portability. Several platforms have been proposed in the past for on-chip ethanol detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Light reflected from the first DMD is naturally Fourier transformed passing through the first Fourier lens at one focal length, f, apart from the first DMD in the object plane. [103][104][105][106][107][108][109][110][111][112][113][114][115][116] The pattern in the second DMD, with particular orientation with respect to the first one, acts as a spatial mask in the Fourier plane, periodically selecting the spatial frequency components of the input image. The frequency filtered image is inverse Fourier transformed into the real space by the second Fourier lens and imaged by a high-speed camera.…”
Section: Resultsmentioning
confidence: 99%
“…Light reflected from the first DMD is naturally Fourier transformed passing through the first Fourier lens at one focal length, f, apart from the first DMD in the object plane. [103][104][105][106][107][108][109][110][111][112][113][114][115][116] The pattern in the second DMD, with particular orientation with respect to the first one, acts as a spatial mask in the Fourier plane, periodically selecting the spatial frequency components of the input image. The frequency filtered image is inverse Fourier transformed into the real space by the second Fourier lens and imaged by a high-speed camera.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported a 11.7% of absorption drop observed on the introduction of gas in a PhCW made using SOI platform. An updated work with 250 ppb detection limit was also reported [98] A 2D rod-type PhCW was also discussed for methane (CH 4 ) detection in the Mid-IR regime [99]. The FDTD analysis was performed for gas concentration of 700 ppm.…”
Section: A Gas Sensingmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49] At the same time, in optics, the Optical Fourier Transform (FT) and dot-product multiplication performed passively by a single lens or metalens have reduced computational complexity compared to logarithmic scaling in electronic processing units, [50][51][52][53][54][55][56] both free-space [57][58][59][60][61][62][63][64][65] and integrated photonic integrated circuits versions. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] The only drawback of Spatial Light Modulators (SLMs) based optical computing systems would be the refresh rate of the device itself, but with recent research progress on novel phase-changing material and other 2D material as well as their corresponding applications, [81][82][83][84][85][86]…”
Section: Introductionmentioning
confidence: 99%